Randomized trial of 'intelligent' autotitrating ventilation versus standard pressure support non‐invasive ventilation: Impact on adherence and physiological outcomes. Issue 4 (24th March 2014) - Kelly, Julia L.; Jaye, Jay; Pickersgill, Rachel E.; Chatwin, Michelle; Morrell, Mary J.; Simonds, Anita K.
Abstract Background and objective Effective non‐invasive ventilation (NIV) therapy is dependent on optimal ventilator settings to maximize clinical benefit and patient tolerance. Intelligent volume‐assured pressure support (iVAPS) is a hybrid mode of servoventilation, providing constant automatic adjustment of pressure support (PS) to achieve a target ventilation determined by the patient's requirements. In a randomized crossover trial, we tested the hypothesis that iVAPS, with automated selection of ventilator settings, was non‐inferior to standard PS ventilation, with settings determined by an experienced health‐care professional, for controlling nocturnal hypoventilation in patients naive to NIV. Methods Eighteen patients referred to a ventilator clinic with chronic obstructive or restrictive lung disease and newly diagnosed nocturnal hypoventilation (10 male, median (interquartile range): age 54(41–61) years, mean daytime PaO2 9.25(8.59–10.31) kPa, ‐PaCO2 6.38(5.93–6.65) kPa were randomized to iVAPS and standard PS. Polysomnography with transcutaneous CO2 monitoring was performed at baseline and 1 month after each treatment period. Nightly hours of therapy were recorded by the ventilator. Results iVAPS delivered a lower median PS compared with standard PS (8.3(5.6–10.4) vs 10.0(9.0–11.4) cmH2O; P = 0.001) for the same ventilatory outcome (mean overnight: SpO2 96(95–98) vs 96(93–97)%; P = 0.13 and PtcCO2 6.5(5.8–6.8) vs 6.2(5.8–6.9); P = 0.54). There was no difference in outcome between ventilator modes for spirometry, respiratory muscle strength, sleep quality, arousals or O2 desaturation index. Adherence was greater with iVAPS (5:40(4:42–6:49) vs 4:20(2:27–6:17) hh:mm/night; P = 0.004). Conclusions iVAPS servoventilation with automation of ventilation settings is as effective as PS ventilation initiated by a skilled health‐care professional in controlling nocturnal hypoventilation and produced better overnight adherence in patients naive to NIV.